Effect of irrigation depths on the productivity of beet cultivated in Alto São Francisco, Minas Gerais (Research, Society and Development, 2021)
The productive arrangements of sugar beet (Beta vulgaris L.) cultivated under irrigation systems neglect techniques that quantify the real water requirement of the crop. Thus, the objective of this work was to investigate whether irrigation depths interfere in the diameter and productivity of sugar beet. The experiment was conducted at the Federal Institute of Minas Gerais (MG), Campus Bambuí, MG, from September to December 2016, with the cultivar EWTT - SK. The treatments consisted of five irrigation management, with application of water depths corresponding to the percentages of crop evapotranspiration of 80%, 90%, 100%, 110% and 120%, supplied manually whenever the soil reached 80% of its real availability. The experimental design was in randomized blocks, with four replications. Sowing was done in Styrofoam trays and the seedlings were transplanted in the soil at 34 days. Harvest was carried out 105 days after sowing. The diameter (mm) and productivity (t ha-1) of beet were evaluated. From the results obtained, it was observed that there was a significant difference for both evaluations, and the treatment with a depth of 120% of the crop evapotranspiration obtained better results in both evaluations, compared to the other treatments. Thus, it is concluded that the increase in the irrigation depth has a direct effect on the diameter and productivity of beet, with the 120% ETc depth showing the best results. The use of smaller blades promotes a reduction in these analyzed characteristics, thus compromising the production of the crop. The results reinforce the importance of irrigation and its management for the production of the crop.